Exploring The Dimensions And Impact Of Consumer Fanaticism On Brand Loyalty: A Literature Review - Qital, Dari Aulia (Journal of Correctional Management, 2024)
This literature review explores the multifaceted nature of consumer fanaticism, its antecedents, and its impact on brand loyalty and marketing strategies. By synthesizing insights from five key studies on consumer fanaticism, this research develops a comprehensive framework for understanding how fanaticism influences consumer behavior and brand management. The findings highlight the dual nature of consumer fanaticism, offering practical implications for marketers aiming to leverage or mitigate its effects